Evidence linking phthalate exposure to alterations of hematologic parameters in Chinese children: A cross-sectional study - Mei-Ting Wei; Ying Wen; Zhu-Xia Zhang; Xiu-Ju Liu; Feng-Xiang Wei; Wei-Qiang Liu; Li Zhou; Ding-Yan Chen; Yao Yao (Environmental Chemistry and Ecotoxicology)
School-aged children are a particularly susceptible population to phthalate exposure, yet research examining the correlation between combined exposure to multiple phthalates and hematologic changes is limited. We explored the individual and joint associations of early childhood phthalate exposure with hematologic parameters. A total of 1053 school-aged children from Shenzhen, China, 6–8 years of age, were enrolled in this cross-sectional study. Nine phthalate metabolites (mPAEs) and four hematologic parameters (white blood cell [WBC] count, red blood cell [RBC] count, hemoglobin [Hb], and platelet [PLT] count) were measured at the same time. To evaluate the connections between mPAEs and hematologic indices, both individually and in combination, several analytical approaches were used, including the generalized linear model (GLM), the Bayesian kernel machine regression (BKMR) model, and the quantile g-computation (QGC) model. The findings of the GLM indicated that the majority of mPAEs were correlated with hematologic parameters. Specifically, higher levels of mono-(2-ethyl-5-oxohexyl) phthalate [MEOHP] (β: –0.021; 95 % CI: −0.029, −0.012) and mono-(2-ethylhexyl) phthalate [MEHP] (β: –0.022; 95 % CI: −0.036, −0.008) were associated with a decreased PLT count. The results of the QGC and BKMR models showed that the mPAE mixture had a negative correlation trend with the PLT count (β = −0.023; P = 0.034). There was also a weak downward trend with the WBC count, RBC count, and Hb concentration. It is worth noting that among the mixed effects, MEOHP and MEHP had the greatest impact on the four hematologic parameters and showed a consistent negative correlation. Our study demonstrated that mPAEs are closely associated with hematologic parameters in school-aged children, especially the PLT count, and identified MEOHP and MEHP as the key contributors to the joint effect. These findings demonstrate the importance of reducing the potential health hazards of phthalate exposure to the hematologic system in children.